Petrochemistry and tectonic setting of mafic volcanic rocks in the Chon Daen-Wang Pong area, Phetchabun, Thailand - Boonsoong A. (2014)
The mafic volcanic rocks and hypabyssal rocks in the Chon Dean-Wang Pong area are possibly the southern extension of the western Loei Volcanic Sub-belt, Northeast Thailand. They are least-altered, and might have been formed in Permian-Triassic times. The rocks are commonly porphyritic, with different amounts of plagioclase, clinopyroxene, orthopyroxene, amphibole, Fe-Ti oxide, unknown mafic mineral, and apatite phenocrysts or microphenocrysts, and are uncommonly seriate textured. The groundmass mainly shows an intergranular texture, with occasionally hyalophitic, intersertal and ophitic-subophitic textures. The groundmass constituents have the same minerals as the phenocrysts or microphenocrysts and may contain altered glass. The groundmass plagioclase laths may show a preferred orientation. Chemically, the studied rock samples can be separated into three magmatic groups: Group I, Group II, and Group III. These magmatic groups are different in values for Ti/Zr ratios. The averaged Ti/Zr values for Group I, Group II, and Group III rocks are 83±6, 46±12, and 29±5, respectively. In addition, the Group I rocks have higher P/Zr, but lower Zr/Nb relative to Group II and Group III rocks. The Group I and Group II rocks comprise tholeiitic andesite-basalt and microdiorite-microgabbro, while the Group III rocks are calc-alkalic andesite and microdiorite. According to the magmatic affinities and the negative Nb anomalies on normal mid-oceanic ridge basalt (N-MORB) normalized multi-element plot, arc-related lavas are persuasive. The similarity between the studied lavas and the Quaternary lavas from the northern Kyukyu Arc, in terms of chondrite-normalized rare earth element (REE) patterns and N-MORB normalized multi-element patterns, leads to a conclusion that the mafic volcanic rocks and hypabyssal rocks in the Chon Daen-Wang Pong area have been formed in a volcanic arc environment. © 2010 Blackwell Publishing Asia Pty Ltd.